History of optical trapping and manipulation of small-neutral particle, atoms, and molecules - Ashkin, A.
The historical review and manipulation of optical trapping and small-neutral particles is reviewed. The impact of the technique on the various subfields of physics, chemistry, and biology is presented. In the light scattering field, the technique led to the highest resolution studies of Mie scattering. Laser trapping and cooling techniques resulted in the optical trapping of individual atoms, Bose-Einstein condensates, and atom lasers with respect to atomic physics. The optical tweezer techniques' usage led to an understanding of the mechanics, force generation, and kinetics of various motor molecules and mechanoenzymes. Colloidal science utilized the ability of tweezers to manipulate small macroscopic particles.
Keywords: ATOMIC PHYSICS; LASER BEAM EFFECTS; LIGHT SCATTERING; MOLECULAR DYNAMICS; OPTICAL INSTRUMENTS